Integration of Local Wisdom Values in Primary School Curriculum for Strengthening Students' Character - Lina Pratiwi (Al Yazidiy Jurnal Sosial Humaniora dan Pendidikan, 2025)
The character crisis in the younger generation is a serious challenge in Indonesian education. One strategic solution is to integrate local wisdom values in the curriculum, especially at the elementary school level, which is the main foundation of character building. This research aims to explore how local wisdom values can be effectively integrated in learning activities to strengthen students' character education. The research method used is descriptive qualitative with a case study approach in one of the public elementary schools in East Java. Data collection techniques were conducted through interviews, classroom observations, and analysis of lesson plan documents. The results showed that the integration of local wisdom values such as gotong royong, courtesy, and responsibility can be done through integrated thematic learning themes, extracurricular activities, and instilling values through folklore and regional cultural practices. Teachers play an important role in the process of internalizing these values, both through active learning methods and exemplary attitudes. The conclusion of this study states that the integration of local wisdom not only strengthens students' character, but also builds a strong cultural identity from an early age. Therefore, policy support and teacher training are needed to develop local culture-based learning materials on an ongoing basis.